2021
DOI: 10.3390/ijerph182312321
|View full text |Cite
|
Sign up to set email alerts
|

Mind-Wandering during Personal Music Listening in Everyday Life: Music-Evoked Emotions Predict Thought Valence

Abstract: Research has shown that mind-wandering, negative mood, and poor wellbeing are closely related, stressing the importance of exploring contexts or tools that can stimulate positive thoughts and images. While music represents a promising option, work on this topic is still scarce with only a few studies published, mainly featuring laboratory or online music listening tasks. Here, I used the experience sampling method for the first time to capture mind-wandering during personal music listening in everyday life, ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 91 publications
(135 reference statements)
4
18
0
Order By: Relevance
“…The musical stimuli were chosen from a prior study (Kuan, Morris, & Terry, 2017) . That said, other genres have also shown strong effects of music on imagination, making this choice somewhat arbitrary Koelsch et al, 2019;Taruffi, 2021). More importantly, the pieces were selected to be associated with a relaxing (piece by Respighi) and an arousing (piece by Shostakovich) emotional state, confirmed in the prior study for the two aforementioned pieces (Kuan et al, 2017).…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…The musical stimuli were chosen from a prior study (Kuan, Morris, & Terry, 2017) . That said, other genres have also shown strong effects of music on imagination, making this choice somewhat arbitrary Koelsch et al, 2019;Taruffi, 2021). More importantly, the pieces were selected to be associated with a relaxing (piece by Respighi) and an arousing (piece by Shostakovich) emotional state, confirmed in the prior study for the two aforementioned pieces (Kuan et al, 2017).…”
Section: Stimulimentioning
confidence: 99%
“…A large proportion of music listeners report that they experience spontaneous imagery when listening to music (Day, Thompson, & Boag, 2019;Vuoskoski & Eerola, 2015). Music is a reliable inducer of spontaneous, undirected mind-wandering (Herbert, 2013; see Taruffi &Fujioka, 2019 for reviews) and listening to music increases the likelihood of mind-wandering episodes to occur (Taruffi, 2021). The characteristics of the music also shapes the content of such mind-wandering episodes (Dahl et al, 2022), with heroic music, for example, being predictive of exciting and positive thoughts, whereas sad music is predictive of demotivating thoughts (Koelsch, Bashevkin, Kristensen, Tvedt, & Jentschke, 2019).…”
Section: Music and Mental Imagery Generationmentioning
confidence: 99%
“…Koelsch and colleagues (2019) found heroic music to evoke more empowering and motivating thoughts in participants, in contrast to the more relaxing or depressing thoughts reported for sad music. Similarly, the experiencesampling study by Taruffi (2021) found that valence of thoughts could be predicted by music-evoked emotions. In a recent study using Indian Carnatic music, Sharma et al (2021) found reduced anxiety scores for participants listening to clips manipulated to vary incrementally in tempo and octave, compared to those listening to clips that had not been manipulated (stable music).…”
Section: Spontaneous Vmimentioning
confidence: 85%
“…The HR is regulated by several reflex pathways in the brainstem and autonomic cardiac nodes, while the latter is influenced by forebrain cortical structures such as the hypothalamus, amygdala, insular cortex, and orbitofrontal cortex ( Esler, 2016 ). Studies have shown that music can induce affective and emotional regulation through structural activity in the anteriorbrain, thereby reducing HR ( Taruffi, 2021 ). As shown in Table 3 , the HR in the intervention group was significantly lower than in the control group, indicating a significant sedative effect of the music intervention on HR.…”
Section: Discussionmentioning
confidence: 99%